2018
DOI: 10.1002/14651858.cd006349.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty for osteoporotic vertebral compression fracture

Abstract: Analysis 1.1. Comparison 1 Efficacy: Vertebroplasty versus placebo (sham), Outcome 1 Pain (0 to 10 point scale).. Analysis 1.2. Comparison 1 Efficacy: Vertebroplasty versus placebo (sham), Outcome 2 Proportion of participants with pain improved by a clinically relevant amount (>2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 110 publications
0
33
0
Order By: Relevance
“…[4,5] Because meta-analysis can offer the highest level of scientific evidence about the efficacy of an intervention based on the principles of evidence-based medicine, in 2015, Buchbinder et al included 11 randomized controlled trials (RCTs) and 1 quasi-RCT conducted in various countries in another study. [68] This review did not support a role for vertebroplasty in the treatment of osteoporotic vertebral fractures in routine practice. In addition, this procedure was indicated to be incapable of restoring the initial height of the vertebral body.…”
Section: Introductionmentioning
confidence: 91%
“…[4,5] Because meta-analysis can offer the highest level of scientific evidence about the efficacy of an intervention based on the principles of evidence-based medicine, in 2015, Buchbinder et al included 11 randomized controlled trials (RCTs) and 1 quasi-RCT conducted in various countries in another study. [68] This review did not support a role for vertebroplasty in the treatment of osteoporotic vertebral fractures in routine practice. In addition, this procedure was indicated to be incapable of restoring the initial height of the vertebral body.…”
Section: Introductionmentioning
confidence: 91%
“…However, leaving aside these potential issues, when data from all five trials were combined in an updated Cochrane review, there was remarkable consistency in results across trials as evident by the paucity of statistical heterogeneity in pooled analyses . High‐ to moderate‐quality evidence based on the five placebo‐controlled trials found that vertebroplasty provides no demonstrable clinically important benefits over placebo in terms of pain, disability, disease‐specific or overall quality of life or participant‐rated global assessment of treatment success.…”
Section: Three Additional Trials Fail To Overturn Conclusion From Thmentioning
confidence: 99%
“…Many hundreds of thousands of patients have received vertebroplasty since the first two high quality randomised trials were published, and many harms have been reported. While the small number of events in controlled trials means there is uncertainty around the exact risk estimates of harms from vertebroplasty, reported harms include infection, rib fractures, further vertebral fractures, cement emboli lodging in the lung or piercing the heart, paralysis and death . A pooled estimate based on data from six controlled trials has suggested that vertebroplasty may be associated with a higher number of new symptomatic vertebral fractures compared with controls (48/418 (95 per 1000; range 34–264) compared with 31/422 (73 per 1000), risk ratio 1.29 (95% confidence interval 0.46–3.62)), although this analysis is also underpowered and therefore uncertain.…”
Section: First Do No Harmmentioning
confidence: 99%
“…The first Cochrane review for vertebroplasty was published in 2015 . This also detailed the review protocol which has not been updated and still applies to the more recent Cochrane review published in 2018.…”
Section: Meta‐analysesmentioning
confidence: 99%
“…This also detailed the review protocol which has not been updated and still applies to the more recent Cochrane review published in 2018. This included 21 trials and declared that high‐ to moderate‐quality evidence suggested vertebroplasty provides no clinically important benefits with respect to pain, disability, QoL or treatment success after 1 month . No mention was made of these outcomes after this time point.…”
Section: Meta‐analysesmentioning
confidence: 99%